The Role Internal Supervision Unit Auditor and Organizational Commitments Toward Good University Governance in Public Service Agency State Universities - Azka Raga, Ridha; Suharman, Harry; Sari, Prima Yusi (Jurnal Organisasi dan Manajemen, 2020)
This research aims to determine the influence of the role internal supervision unit and also organizational commitment to achieving Good University Governance. The population of this research was 23 state universities in Indonesia with BLU status under The Ministry of Research, Technology, and Higher Education. The Audit Board of The Republic of Indonesia (BPK-RI) found low-quality performance findings to the acceptance a qualified opinion (WDP) BPK RI accompanied by findings of misappropriation of financial statement records in 2015.This is due to the low quality of governance performance universities, which often occur at Public Service Agency of State University as well as a lack of transparency and accountability. The sampling technique used in this research was purposive sampling and the method for analyzing data was path analysis. Findings. The results showed that there was a significant positive influence and were supported by the role of the internal supervision unit and organizational commitment to the achievement of good university governance. Moreover, this study also saw a positive influence on the role of the internal supervision unit to achieve good university governance through organizational commitment.